NILAI BUDAYA DAN EKSISTENSI SASTRA LISAN DAYAK GOLIK DI KABUPATEN SANGGAU - Hari Purwiati (tuahtalino, 2020)
This study is entitled Cultural Values and the Existence of Oral Literature in Dayak Golik in Sanggau Regency. This study aims to obtain a complete picture of the cultural values contained in Dayak Golik oral literature and its existence at the present time. The theory used in this study is the concept of cultural values. Cultural values in the form of ideas that conceptualize most valuable in the fabric of people's lives. A cultural value system consists of conceptions that live and grow in the minds of most members of the community and that too is closely related to the things they consider to be very valuable in life. This research is a qualitative research in the literature perspective. The approach used in this study is a cultural and sociological approach. The cultural approach is used to analyze cultural values in the oral text of the Dayak Golik stories. Meanwhile, a sociological approach to analyzing the existence of oral literature at the present time in society. Data analysis shows that there are several cultural values which are contained from two oral literatures which are sampled. In the oral literature entitled The Seven Brothers, the value of bubaya contained includes always doing good to other creatures, pitying you, not being jealous, and being patient in facing trials. Meanwhile in the oral literature of Tangraya Cave the cultural values that exist include patience in facing trials, repaying evil with kindness, not being too greedy in life, and respecting guests.